Multi-floor indoor location estimation system based on wireless local area network [electronic resource] - 422018 Chua, Tien Han (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2007